Albumin Nanoparticle Formulation for Heart-Targeted Drug Delivery: In Vivo Assessment of Congestive Heart Failure - Nikita Lomis; Ziyab K. Sarfaraz; Aiman Alruwaih; Susan Westfall; Dominique Shum-Tim; Satya Prakash (MDPI AG, 2021)
Congestive heart failure is a fatal cardiovascular disease resulting in tissue necrosis and loss of cardiac contractile function. Inotropic drugs such as milrinone are commonly used to improve the myocardial contractility and heart function. However, milrinone is associated with severe side effects and lower circulation time. In this article, a novel protein nanoparticle formulation for heart-targeted delivery of milrinone has been designed and tested. The formulation was prepared using albumin protein conjugated with the targeting ligand, angiotensin II peptide to form nanoparticles following the ethanol desolvation method. The formulation was characterized for size, charge, and morphology and tested in a rat model of congestive heart failure to study pharmacokinetics, biodistribution, and efficacy. The overall cardiac output parameters were evaluated comparing the formulation with the control non-targeted drug, milrinone lactate. This formulation exhibited improved pharmacokinetics with a mean retention time of 123.7 min, half-life of 101.3 min, and clearance rate of 0.24 L/(kg*h). The targeted formulation also significantly improved ejection fraction and fractional shortening parameters thus improving cardiac function. This study demonstrates a new approach in delivering inotropic drugs such as milrinone for superior treatment of congestive heart failure.